Resilience for a World in Flux - Glass, Chris R. (Journal of International Students, 2017)
The rise of nationalism worldwide has led many international researchers to reflect on their role as educators and leaders. Resilience is vital during such tumultuous times. The popular definition of resilience is the capacity to quickly recover from difficulties and setbacks. The term is often misunderstood for a type of sturdy individualism that some people possess more than others or the immunity from stress and negative emotions. There is another, more empirically-based, understanding of resilience. Diane Coutu (2002) outlines three dimensions of resilience: (a) a staunch acceptance of reality; (b) deep belief buttressed by strongly held values; and (c) an uncanny ability to improvise. I believe, as international researchers and educators, we must be resilient in a world where the policies and politics around international students are increasingly in flux.